The Participle kolaphizomenoi in "Martyrium Polycarpi" 2.4 and 2Cor 12:1-10 - Kozlowski, Jan M. (Vigiliae Christianae, 2018)
There is no consensus among editors and translators of Martyrium Polycarpi regarding what reading should be accepted in 2.4: κολαζόµενοι or κολαφιζόµενοι. A hitherto unnoticed intertextual reference to 2Cor 12:1-10 is proposed as an argument in favor of the reading κολαφιζόµενοι. Moreover, detecting this allusion deepens our understanding of the theology of martyrdom in Martyrium Polycarpi.